Attenuation model for aging performance resistance of conductive asphalt concrete. (May 2014) - Tang, N.; Wu, S. P.; Sun, C. J.; Tu, L. L.
Abstract : The aging performance of pavement materials will decay gradually whether or not subjected to load. Conductive asphalt concrete (CAC) is a novel functional asphalt concrete that can be applied to self-monitoring or snow melting due to its intelligent characteristics. An aging testing method has been designed according to the standard testing method of SHRP, AASHTO and China. Dynamic stiffness modulus resistance data of specimens were measured by dynamic indirect tensile test, of which the results indicate that a higher aging temperature will lead to a higher aging degree. The translocation factor of stiffness modulus will not vary with aging temperature T . An attenuation model curve for aging performance resistance of CAC has been established to simulate the variation of aging with resistance for the fatigue self-monitoring of asphalt pavement.